THE CORRELATION BETWEEN RECEPTIVE VOCABULARY AND LITERAL COMPREHENSION IN ENGLISH LANGUAGE LEARNING AT SMPN SATAP 5 RUMBIA JENEPONTO - Sasmita, Andi Elisa Dian; Qalbi, Nur; Muhsin, Muh Arief (FKIP Unismuh Makassar, 2024)
This research aimed to know the correlation between students' Receptive Vocabulary and Literal Comprehension. The subject of this research consisted of 20 students in the 9th grade in SMPN Satap 5 Rumbia Jeneponto. Correlation research was conducted using research design. The questionnaire was the tool utilized to get the data.The results of this study are the students have balance skills in receptive vocabulary. They are not good at applying their receptive vocabulary. And second, the students have good skills in literal comprehension, the students have good skills in literal comprehension as well. They can understand and analyze the main idea and supporting idea in a text. Therefore based on the data above, the researcher found that there was a signicant correlation between the students' receptive vocabulary and literal comprehension in the 9th-grade students of SMPN Satap 5 Rumbia. The Pearson correlation was found to be r oxy = 0.552, which is considered sufficient correlation in the range of 0.400 to 0.599 for standard correlation. It means that there is a correlation between students' receptive vocabulary and literal comprehension. Therefore, the student's receptive vocabulary inuences their literal comprehension, as much their receptive vocabulary the better their literal comprehension.